DNA Sequencing And Phylogenic Tree Analysis Of 16S Rrna And Bla-Oxa-50 Genes Of Carbapenem Resistant Pseudomonas Aeruginosa In Diwanyah City/ Iraq - Ali Sabri Jabbar; Ahmed Majeed Abdzaid (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Pseudomonas aeruginosa is a major nosocomial pathogen known for its multidrug resistance, including carbapenems. This study aimed to investigate the prevalence of carbapenem resistance in P. aeruginosa of clinical sources and sequencing of 16S rRNA and blaOXA-50 genes Methods: A total of 53 P. aeruginosa isolates from burn, wound, urinary tract, and ear infections were analyzed. Antibiotic susceptibility testing identified carbapenem-resistant isolates. Polymerase Chain Reaction (PCR) detected 16S rRNA and blaOXA-50 genes, followed by DNA sequencing and phylogenetic analysis of 16S rRNA. Results: Among the isolates, 20 (37.73%) originated from wounds, 16 (30.19%) from burns, 10 (18.9%) from urinary tracts, and 7 (13.20%) from ears. Notably, 12 isolates (22.64%) exhibited carbapenem resistance. All carbapenem-resistant isolates harbored both 16S rRNA and blaOXA-50 genes. 16S rRNA sequencing demonstrated 99.66% homology to known P. aeruginosa strains, further confirmed by phylogenetic analysis. The blaOXA-50 gene displayed high sequence identity (98%-100%) with isolates from Russia, suggesting a potential clonal relationship. Conclusion: A moderate prevalence of carbapenem-resistant P. aeruginosa was revealed by this study and based on 16S rRNA and blaOXA-50 genes sequencing, these strains offered a high genetic similarity compared to the global strains. Further investigation is required to determine the role of blaOXA-50 carbapenem resistance in this bacterium.